2021
DOI: 10.1021/acs.jmedchem.1c00554
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Quinoxaline-Based P1–P3 Macrocyclic NS3/4A Protease Inhibitors with Potent Activity against Drug-Resistant Hepatitis C Virus Variants

Abstract: The three pan-genotypic HCV NS3/4A protease inhibitors (PIs) currently in clinical usegrazoprevir, glecaprevir, and voxilaprevirare quinoxaline-based P2–P4 macrocycles and thus exhibit similar resistance profiles. Using our quinoxaline-based P1–P3 macrocyclic lead compounds as an alternative chemical scaffold, we explored structure–activity relationships (SARs) at the P2 and P4 positions to develop pan-genotypic PIs that avoid drug resistance. A structure-guided strategy was used to design and synthesize two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 47 publications
0
9
0
1
Order By: Relevance
“…Over the years, we and others have shown that regions where inhibitors protrude from the substrate envelope are susceptible to resistance mutations 16 , 26 , 28 , 37 40 . Thus, our newly determined substrate envelope of M pro provides a predictive tool to assess likelihood that resistance to a specific inhibitor will emerge.…”
Section: Resultsmentioning
confidence: 99%
“…Over the years, we and others have shown that regions where inhibitors protrude from the substrate envelope are susceptible to resistance mutations 16 , 26 , 28 , 37 40 . Thus, our newly determined substrate envelope of M pro provides a predictive tool to assess likelihood that resistance to a specific inhibitor will emerge.…”
Section: Resultsmentioning
confidence: 99%
“…162 Next, P1−P3 macrocyclization was explored as P1−P3 cycles better accommodate the A156T mutation and allow flexibility of the P2 moiety. 58 Inhibitors containing the 3-methyl-quinoxaline group at the P2 Pro, in combination with several P4capping groups, were prepared. Almost all the compounds retained low antiviral potency against the A156T variant (nanomolar range).…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 99%
“…The first generation of HCV PIs includes agents with potent activity against gt1; unfortunately, they were not effective against all genotypes. The precursors of first generation PIs were N-terminal peptide products derived from the cleavage of sequences of HCV NS3 protease substrates, corresponding to the P6–P1 residues from the NS4A/4B and NS4B/5A, also-called breakthrough structures. , These inhibitors were transition state mimics and were found to act as competitive inhibitors of the enzyme (feedback inhibition). Later, less peptidelike product-based ones were designed, by peptide truncation and extension of the side chain of the P2 proline (Pro) site and by P1 optimization.…”
Section: Hcv Ns3 Pis: Development Of Inhibitors Of First Second and T...mentioning
confidence: 99%
“…The macrocyclic scaffold structure shared by approved HCV NS3/4A protease inhibitors has been modified to modulate both potency and drug-like properties of the inhibitors as well as prevent resistance due to pre-existing resistance-associated substitutions (RASs) and/or baseline polymorphisms among diverse genotypes. 200 , 201 …”
Section: Hepatitis C Virus (Hcv)mentioning
confidence: 99%